Penggunaan Teknologi Augmented Reality pada Aplikasi Bangun Ruang Sederhana Berbasis Unity dan Vuforia Engine - Fahmy Syahputra; Teuku Naufal; Echon Haqnizo; Wahyu Ramadhi; Naomi Pranatasyah; Fauzan Fachruzi; Rivany Virenzia (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Advances in augmented reality (AR) technology have opened up new possibilities in learning, such as help with mathematics. The aim of this research is to develop a simple interactive learning application for building rooms based on AR technology using Unity and Vuforia Engine. This application is designed to help students understand spatial geometry concepts visually and interactively so as to increase interest and understanding of the subject matter. This application development uses Unity as a development platform and Vuforia Engine as an SDK to facilitate AR integration. This application creates a more interesting learning experience and supports the visualization of geometric objects such as cones, cubes, tubes, balls and pyramids. AR technology allows students to interact with these objects in a 3D environment, which can be very helpful in clarifying concepts and formulas that are difficult to understand using traditional learning media. It is hoped that this research can provide innovative solutions to improve the quality of geometry learning in schools.